El teocintle en Mexico: distribucion y situacion actual de las poblaciones. Teosinte in Mexico: distribution and present status of populations - Sánchez G, J.; Ordaz S, L. (1987)
During a collecting mission in 1986, 103 accessions were taken from the principal areas of distribution of teocintle. This is a record of the trip and the material collected and an analysis of the data.